PREDIKSI BENTUK AWAN BERDASARKAN KRITERIA CURAH HUJAN DI PERAIRAN CILACAP - Lusiani (Saintara: Jurnal Ilmiah Ilmu-Ilmu Maritim, 2019)
The goal to be achieved in this paper is to predict the form of cloud based on rainfall criteria in Cilacap waters. (1. Group of nimbostratus clouds, stratus, altostratus, 2. Group of stratocumulus and altocumulus clouds 3. Cumulus and cumulonimbus cloud groups). The method in this study is a combination of survey and literature review. In this study the authors take the location in the waters of Cilacap. The data used are secondary data obtained from the Central Bureau of Statistics of Cilacap Regency. Sample data used is statistical data within the period of 5 years starting from 2012 until 2016. Based on the data analysis that has been done, namely the classification or classification of rainfall intensity data within the period of 5 years (2012-2016) obtained detailed data that is : In 2012 the average rainfall intensity of 10.6mm with rainfall criteria including light rain then belongs to the cloud form of Stratocumulus, altocumulus; In 2013 the average intensity of 11.1mm rainfall with rainfall criteria including light rain then belongs to the cloud form of Stratocumulus, altocumulus; In 2014 the average rainfall intensity of 13.5mm with rainfall criteria including light rain then belongs to the cloud form of Stratocumulus, altocumulus; By 2015 the average rainfall intensity of 10.3mm with rainfall criteria including light rain then includes the Stratocumulus cloud form group, altocumulus; In 2016 the average rainfall intensity of 18.4mm with rainfall criteria including light rain then belongs to the cloud form of Stratocumulus, altocumulus. Based on the details of the data, it can be concluded that the prediction of cloud form based on rainfall that occurs in the waters of cilacap is the group of stratocumulus and altocumulus cloud form.